Economic Aspects of the Boulder Dam Project - Homan, Paul T. (Quarterly Journal of Economics, 1931)
I. Complexity of the issues, 177. — II. The Colorado River Basin, 181; Interests of the Imperial Valley in the project, 181; Interests of Los Angeles and neighboring cities, 183. — III. Interests of the Upper-Basin States, 185; The Colorado River Compact, 188; Arizona's interests, 188. — IV. Cost estimates and other figures, 191. — V. Administrative aspects of the Boulder Dam project act, 192; Financial provisions of the act, 194. — VI. Contracts for the allocation of electrical power rights, 197; Comparison of costs of hydro-electric and steam-generated power, 200; Total financial cost to the Los Angeles area, 202. — VII. Fundamental questions. (1) Long-run economic expediency, 205; (2) Immediate economic expediency, 206; (3) Political expediency, 209; (4) The policy of federal enterprise in the power industry, 213; Conclusion, 216.